The possibility of a sustainable development of culture - Sztumski, Wiesław (Folia Philosophica, 2002)
The progress of knowledge and technology has damaged the original unity of the material and spiritual culture which existed in antiquity. A particular role in the split of these two subordinating branches of culture, and in their disproportionate development was played by the paradigm of scientism in the period of the Enlightenment, and, later and up till now, by the paradigm of commercialism. The material culture became more quickly a commodity than the spiritual culture which only recently was made to obey the rules of a free market economy. Consequently, the material culture developed at a much faster rate than the spiritual culture. In such circumstances, it is difficult to talk about a balanced development of culture as a whole. Nevertheless, there has appeared a chance for a balanced and harmonious development of both cultures within the framework of the ecological paradigm which, in the future, is sure to replace the paradigms of scientism and commercialism that have been hitherto considered valid.